Identifying Students’ Diction Errors in Translating News: A Case Study in a Genre-Based Translation Class - M. T. Kariadi; Dyah Raina Purwaningsih; Tri Wahyu SP (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2017)
Genre-Based Translation is one of the required courses in semester 6 should be taken by all students of English Study Program of Jenderal Soedirman University, Purwokerto. In this course, students are given more translation practices on both fiction and non-fiction texts. News is considered as one genre of non fiction texts. Specific dictions applied in the news articles are relatively complex that they shouldnot only beclearly but also concisely translated. Nowadays, students are required to be able to accurately,acceptably, and readably transfer the messagesin the forms of dictions from the source to the target language. However, this research focuses more on the acceptability of dictionsasthe right dictionsinfluence the acceptability of the whole text. The article discusses the students’ translation results of a news text entitled Deutsche Bank to raise $8.6btaken from The Jakarta Post, published on March 21, 2017. This research belongs to descriptive-qualitative research using a total purposive sampling techniquein determining the texts used to analyze the data.